Process for the preparation of a polyamide resin composite

CN122958855APending Publication Date: 2026-10-23YICHUN EXCELLENT CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610908718.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-23

Smart Images

  • Figure CN122958855A_ABST
    Figure CN122958855A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer material preparation, in particular to a preparation process of polyamide resin composite material. The polyamide resin composite material comprises polyamide resin, flat glass fiber, maleic anhydride grafted polyolefin elastomer, flame retardant system and functional additives; wherein the flame retardant system is composed of aluminum diethyl hypophosphite, aluminum phosphite and DOPO-g-PDA@SiO2 particles. In the preparation, DOPO is grafted on the surface of PDA@SiO2 to obtain DOPO-g-PDA@SiO2 particles; then the components are uniformly mixed, melt blended by a double screw extruder, and flat glass fiber is added through a side feeding port, and then extruded and granulated to obtain the product. The ternary synergistic flame retardant system of aluminum diethyl hypophosphite, aluminum phosphite and DOPO-g-PDA@SiO2 makes the composite material meet the stringent requirements of high flame retardancy, high leakage resistance tracking resistance and long life thermal stability of high voltage connectors for new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer material preparation technology, specifically to a preparation process for a polyamide resin composite material. Background Technology

[0002] High-voltage connectors for new energy vehicles are key components that enable electrical connections and signal transmission between core components such as battery packs, motor controllers, and high-voltage distribution boxes. Their housings and insulating structures are primarily injection molded from thermoplastic engineering plastics. Currently, high-performance polyamide materials such as polyphthalamide, polyphenylene sulfide, and high-temperature polyamides have become the mainstream materials for high-voltage connectors due to their excellent heat resistance, mechanical strength, and electrical insulation properties. Among them, polyamide resins, represented by PA10T / 66 copolymer, can meet the basic requirements for dimensional stability and flame-retardant safety of connectors through flat glass fiber reinforcement and flame-retardant modification.

[0003] However, during the long-term service of new energy vehicles, high-voltage connectors are subjected to harsh environments with high temperatures (120℃~150℃), high voltage (800V platform), high humidity, and temperature fluctuations (-40℃~150℃ cycle). Traditional flame-retardant reinforced polyamide materials have exposed the following prominent problems: it is difficult to achieve both flame retardancy rating and high tracking index. Conventional halogen-free flame retardants (such as aluminum diethylphosphite and melamine cyanurate) require high filler content to achieve the UL94 V-0 rating, but high filler content will reduce the tracking index (often below 500V), which cannot meet the safety requirements of high-voltage connectors for tracking resistance. After long-term aging at high temperatures, the flame retardancy and mechanical properties degrade significantly. Small molecule flame retardants are prone to migration, volatilization, or decomposition during the 150℃ thermo-oxidative aging process, causing the flame retardancy rating to drop from V-0 to V-2 or even burn and drip. At the same time, the mechanical strength retention rate is often below 60%, leading to brittle fracture of the connector shell.

[0004] To address these issues, existing technologies attempt to improve flame retardant efficiency and thermal stability by compounding flame retardant synergists and introducing nanoparticles. For example, diethylaluminum hypophosphite is compounded with aluminum phosphite (chemical formula Al2(HPO3)), utilizing the synergistic effect of the gas-phase flame retardancy of diethylaluminum hypophosphite and the condensed-phase char formation of aluminum phosphite to achieve a V-0 rating with a lower filler content; or nano-silica is added to the system as a char-forming enhancer to improve the density of the char layer through physical blending. Studies have found that the diethylaluminum hypophosphite / aluminum phosphite binary system still struggles to stably pass the V-0 test in thin-walled (1.6 mm) parts, and the char layer is loose and prone to dripping during combustion; while directly adding unmodified nano-silica results in high surface energy, poor compatibility with the polyamide matrix, and easy agglomeration during high-temperature processing. In addition, some studies have attempted to introduce 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as a gas-phase flame retardant, but DOPO is prone to sublimation and volatilization during high-temperature processing and long-term thermal aging, making it difficult to maintain its flame-retardant effect.

[0005] However, none of the aforementioned individual or binary flame-retardant systems can simultaneously resolve the contradictions between flame-retardant efficiency, thermal aging stability, and interfacial compatibility at the molecular / nanoscale level. The diethylaluminum hypophosphite / aluminum phosphite binary system offers limited improvement in flame-retardant retention after high-temperature aging; unmodified nano-silica exhibits poor dispersibility and lacks synergistic interfacial design with diethylaluminum hypophosphite and aluminum phosphite; and ordinary DOPO is volatile and difficult to stably exert its flame-retardant effect during long-term service. Therefore, existing technologies still cannot simultaneously achieve the comprehensive requirements of UL94 V-0 flame retardant rating, CTI≥600V, and a flame-retardant and mechanical property retention rate ≥80% after 150℃×1000h thermal aging, making it difficult to meet the high reliability and high safety requirements of high-voltage connectors for new energy vehicles under high-temperature, high-voltage, and long-life operating conditions. Summary of the Invention

[0006] To address the above problems, the present invention provides a preparation process for polyamide resin composite materials, comprising the following steps: S1. Dissolve DOPO and GPTMS in anhydrous toluene at a mass ratio of (1.2~1.8):1, where the mass ratio of anhydrous toluene to DOPO is (5~10):1. Add 1%~5% (by mass of DOPO) of triethylamine. Reflux the mixture at 100~120℃ for 6~12 hours under nitrogen protection, with a nitrogen flow rate of 0.1~0.5 L / min. After the reaction, remove the solvent by vacuum distillation to obtain the DOPO derivative. Disperse PDA@SiO2 particles in anhydrous toluene solvent, where the mass ratio of anhydrous to PDA@SiO2 particles is (10~20):1. Add the DOPO derivative and DOPO derivative... 0.5%–2% triethylamine (by biological mass), DOPO derivative and PDA@SiO2 particles were reacted at 100–120 °C for 6–12 hours under nitrogen protection at a nitrogen flow rate of 0.1–0.3 L / min. After the reaction, the particles were centrifuged at 8000–10000 rpm for 10–20 minutes, washed 2–4 times with anhydrous ethanol, and dried at 75–85 °C under a vacuum of -0.02–-0.01 MPa for 12 hours to finally obtain DOPO-g-PDA@SiO2 particles. GPTMS was 3-glycidyl etheroxypropyltrimethoxysilane, and PDA was polydopamine.

[0007] The reaction is carried out in toluene solvent. The trace amount of water in the reaction system (water content controlled within the range of 0.05%~0.1%) facilitates the hydrolysis of trimethoxysilyl groups to generate silanols, which then undergo a condensation reaction with the PDA@SiO2 surface-active groups. No additional molecular sieve is required for water removal, nor is strict anhydrous treatment of the toluene necessary.

[0008] S2. By weight, mix 55-60 parts of polyamide resin, 11-15 parts of flame retardant system, 3-4 parts of maleic anhydride grafted polyolefin elastomer, and 2-4 parts of functional additives at 800-1200 rpm for 3-5 minutes to obtain a mixture; use a twin-screw extruder for melt blending extrusion, add the mixture to the extruder through the main feed port, and at the same time add 18-21 parts of flat glass fiber with an aspect ratio of 4:1 to the extruder through the side feed port to obtain the polyamide resin composite material.

[0009] The flame retardant system includes a flame retardant and a flame retardant synergist. The flame retardant is 8-10 parts of aluminum diethylphosphite, and the flame retardant synergist is 2-3 parts of aluminum phosphite and 1-2 parts of DOPO-g-PDA@SiO2 particles.

[0010] Preferably, the polyamide resin is one or two of polyamide 9T, polyamide 10T, polyamide 12T, and polyamide 10T / 66 copolymer.

[0011] Preferably, the polyamide resin is a polyamide 10T / 66 copolymer, and the mass ratio of polyamide 10T to polyamide 66 is (13~17):(3~7).

[0012] Preferably, the functional additives include 0.5-1 parts of antioxidant, 0.2-0.5 parts of lubricant, 0.3-0.5 parts of acid absorber, 0.5-1 parts of colorant, 0.2-0.5 parts of nucleating agent, and 0.3-0.5 parts of chain extender.

[0013] Preferably, the antioxidant includes hindered phenolic antioxidants, phosphite antioxidants, and copper salt heat stabilizers; the hindered phenolic antioxidants are selected from one or more of antioxidant 1098, antioxidant 1076, and antioxidant 1010; the phosphite antioxidants are selected from one or more of antioxidant 168 and antioxidant 626; and the copper salt heat stabilizers include a combination of cuprous iodide and potassium iodide.

[0014] Preferably, the antioxidant comprises antioxidant 1098, antioxidant 168 and copper salt heat stabilizer; wherein antioxidant 1098 is 0.2 to 0.4 parts, antioxidant 168 is 0.2 to 0.4 parts, and copper salt heat stabilizer is 0.1 to 0.2 parts.

[0015] Preferably, the lubricant is one or more of pentaerythritol stearate and silicone masterbatch.

[0016] Preferably, the acid absorber is zinc oxide; the colorant is black masterbatch; the nucleating agent is talc; and the chain extender is ADR-4468.

[0017] Preferably, the PDA@SiO2 particles are prepared by the following method: 50-200 nm nano-SiO2 particles are dispersed in 0.01 mol / L tris(hydroxymethyl)aminomethane buffer solution at pH 8-9, with a mass ratio of nano-SiO2 to tris(hydroxymethyl)aminomethane buffer solution of 1:(50-100). The dispersion is ultrasonically carried out for 30 minutes at a power of 180-200 W and a frequency of 40-45 kHz. Dopamine hydrochloride is added, with a mass ratio of dopamine hydrochloride to nano-SiO2 of (1-2):1. The mixture is stirred and reacted at 25-40℃ and 200-400 rpm for 24 hours. After the reaction, the mixture is centrifuged at 10000-15000 rpm for 20-30 minutes, washed 2-3 times, and dried at 50-60℃ and a vacuum of -0.02 to -0.01 MPa for 12 hours to obtain PDA@SiO2 particles.

[0018] Preferably, the temperatures of the twin-screw extruder in zones one through six are: 275~285℃, 280~290℃, 280~290℃, 275~285℃, 265~275℃, and 255~265℃; and the screw speed is 280~320 rpm.

[0019] The present invention has at least one of the following technical effects: 1. The present invention uses a ternary synergistic flame retardant system of diethylaluminum hypophosphite, aluminum phosphite and DOPO-g-PDA@SiO2 to enable the composite material to achieve UL94V-0 rating and CTI≥600V with a thickness of 1.6mm; after heat aging at 150℃×1000h, it still maintains V-0, tensile strength retention rate ≥80%, and CTI retention rate ≥90%, thus solving the problem of flame retardant performance decay and mechanical degradation during long-term service at high temperature.

[0020] 2. The diethylaluminum hypophosphite, aluminum phosphite, and DOPO-g-PDA@SiO2 particles in the flame retardant system work synergistically during combustion: the phosphorus components capture free radicals and suppress flames in the gas phase, and catalyze char formation in the condensed phase; nano-silica enhances the density and thermal stability of the char layer, thereby achieving highly efficient flame retardancy.

[0021] 3. The flat glass fibers are oriented along the melt flow direction, significantly reducing the anisotropic shrinkage of the composite material and thus suppressing warpage in the injection-molded product. Simultaneously, the maleic anhydride-grafted polyolefin elastomer acts as a toughening agent, its rubber phase absorbing the internal stress caused by the difference in thermal expansion coefficients between the glass fibers and the polyamide matrix. The synergistic effect of these two components enables the composite material to maintain good dimensional stability and impact resistance over a wide temperature range, meeting the stringent requirements of high-voltage connectors for precise fit. Attached Figure Description

[0022] Figure 1 This is a SEM image of the DOPO-g-PDA@SiO2 particles prepared in Example 1. Detailed Implementation

[0023] The present invention will now be described in detail through specific embodiments. However, these illustrative embodiments are for purposes and uses only to illustrate the invention and do not constitute any limitation on the actual scope of protection of the invention, nor are they intended to limit the scope of protection of the invention to these embodiments. All equivalent transformations or simple substitutions made based on the substantive content of this application should fall within the scope of protection of this application. For parameter ranges not mentioned, intermediate values ​​are selected. Furthermore, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition.

[0024] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise. Example Example

[0025] S1. 5g of 100nm nano-SiO2 particles were dispersed in 0.01mol / L tris(hydroxymethyl)aminomethane buffer solution (pH=8.5, 375mL). The mixture was ultrasonically dispersed for 30 minutes at a power of 190W and a frequency of 42kHz. 7.5g of dopamine hydrochloride was added, and the mixture was stirred at 30℃ and 300rpm for 24h. After the reaction was completed, the mixture was centrifuged at 12500rpm for 25min, washed 3 times, and dried at 55℃ and a vacuum of -0.015MPa for 12h to obtain PDA@SiO2 particles. 15g of DOPO and 10g of GPTMS were dissolved in 120mL of anhydrous toluene. 0.45g of triethylamine was added, and the mixture was refluxed at 110℃ for 10 hours under nitrogen protection with a nitrogen flow rate of 0.3L / min. After the reaction, the solvent was removed by vacuum distillation to obtain the DOPO derivative. 10g of the PDA@SiO2 particles obtained above were dispersed in 150mL of anhydrous toluene. 20g of the DOPO derivative and 0.2g of triethylamine were added, and the mixture was reacted at 110℃ for 10 hours under nitrogen protection with a nitrogen flow rate of 0.2L / min. After the reaction, the mixture was centrifuged at 9000rpm for 15 minutes, washed three times with anhydrous ethanol, and dried at 80℃ and a vacuum of -0.015MPa for 12 hours to finally obtain DOPO-g-PDA@SiO2 particles.

[0026] DOPO-g-PDA@SiO2 particles were observed using a scanning electron microscope, such as... Figure 1 As shown, the particles are uniformly spherical with complete surface coating, good dispersion, and no obvious agglomeration, proving that a core-shell structured nano flame retardant synergist has been successfully synthesized.

[0027] Under alkaline conditions, the PH bond in DOPO undergoes nucleophilic ring-opening addition to the epoxy group of GPTMS, generating a DOPO derivative containing a trimethoxysilyl group. The trimethoxysilyl group of this derivative undergoes partial hydrolysis in the reaction system to generate silanol (Si-OH), which then undergoes a condensation reaction with active groups such as phenolic hydroxyl and amine groups on the surface of PDA@SiO2 particles to form a stable covalent graft.

[0028] The polydopamine (PDA) coating layer of this invention not only serves as a grafting platform for DOPO but also plays a crucial interfacial bridging role in the composite material. The PDA surface is rich in catechol hydroxyl and amino active groups, which can form hydrogen bonds with the amide groups of the polyamide resin, and can also chemically react or physically entangle with the anhydride groups in the maleic anhydride-grafted polyolefin elastomer. This multi-interfacial interaction significantly improves the compatibility between DOPO-g-PDA@SiO2 particles and the polymer matrix, avoids the aggregation of nanoparticles during high-temperature processing, and reduces the interfacial defect density.

[0029] The nano-SiO2 particles of DOPO-g-PDA@SiO2 have high insulation properties and form a physical barrier after being dispersed on the matrix surface, hindering the continuous development of carbonization channels. The dense carbon layer formed by aluminum phosphite exhibits higher resistivity during the electro-tracking process. The total addition of the three flame retardant components is controlled at 11-15 parts, which is much lower than that of conventional halogen-free flame retardants (usually more than 20 parts are needed to achieve V-0), which helps to reduce the absolute content of ionic substances, thereby improving the CTI value.

[0030] S2. 45 parts PA10T, 13 parts PA66, 3.5 parts maleic anhydride-grafted polyolefin elastomer, 8.5 parts diethyl aluminum hypophosphite, 2.5 parts aluminum phosphite, 2 parts DOPO-g-PDA@SiO2 particles, 0.3 parts antioxidant 1098, 0.3 parts antioxidant 168, 0.15 parts copper salt heat stabilizer, 0.35 parts pentaerythritol stearate, 0.4 parts zinc oxide, 0.8 parts black masterbatch, 0.35 parts talc, and ADR-4468. 0.35 parts were mixed at 1000 rpm for 4 minutes to obtain a mixture. A twin-screw extruder was used for melt blending extrusion. The mixture was fed into the extruder through the main feed port, while 20 parts of flat glass fiber with an aspect ratio of 4:1 were fed into the extruder through the side feed port. The extruder temperatures were as follows: Zone 1 280℃, Zone 2 285℃, Zone 3 285℃, Zone 4 280℃, Zone 5 270℃, Zone 6 260℃, and the die head 275℃; the screw speed was 300 rpm, and the vacuum degree was -0.07 MPa. The extruded strip was water-cooled (15℃), air-dried, and pelletized to obtain composite material particles. The particles were dried in a 90℃ forced-air drying oven for 4 hours and then injection molded into standard test strips.

[0031] Under the high temperature and high shear of a twin-screw extruder, the anhydride groups in maleic anhydride-grafted polyolefin elastomer react with the terminal amino groups of polyamide resin to form a graft copolymer, improving the compatibility between polyamide and elastomer and the interfacial bonding of glass fibers. The flat glass fibers are oriented along the melt flow direction, giving the composite material good dimensional stability. During the combustion heating process (300~400℃), diethylaluminum hypophosphite decomposes to generate diethylphosphite gas and aluminum phosphate residue. The phosphorus-containing gas enters the gas phase to capture H· and OH·, inhibiting flame propagation; aluminum phosphite decomposes to generate amorphous aluminum phosphate and releases a small amount of phosphine. The phosphine is further oxidized to phosphorus-containing oxyacids, promoting the cross-linking of the polyamide matrix into carbon. Within this temperature range, DOPO-g-PDA@SiO2: ① DOPO releases additional phosphorus-containing free radicals, forming a gas-phase flame-retardant superposition effect with ADP; ② The PDA layer carbonizes to form a carbon layer skeleton; ③ Nano-SiO2 fills the pores of the carbon layer, improving the density and thermal oxidation stability of the carbon layer. The three phases work together in a sequential manner of “gas phase-gas phase + condensed phase-condensed phase enhancement”, which enables the 1.6mm thin-walled sample to extinguish rapidly during combustion without dripping, and the carbon layer is complete and dense. Example

[0032] The difference from Example 1 is that the polyamide resin is 55 parts (43 parts PA10T and 12 parts PA66), and the rest of the preparation steps are the same as in Example 1. Example

[0033] The difference from Example 1 is that the polyamide resin is 60 parts (47 parts PA10T and 13 parts PA66), and the rest of the preparation steps are the same as in Example 1. Example

[0034] The difference from Example 1 is that 1.5 parts of DOPO-g-PDA@SiO2 particles were used, while the rest of the preparation steps were the same as in Example 1. Example

[0035] The difference from Example 1 is that: 3.0 parts of aluminum phosphite were used, while the rest of the preparation steps were the same as in Example 1. Example

[0036] The difference from Example 1 is that when preparing DOPO-g-PDA@SiO2 particles, the mass ratio of DOPO derivative to PDA@SiO2 is 1.5:1, and the remaining preparation steps are the same as in Example 1.

[0037] Comparative Example Comparative Example 1 The difference from Example 1 is that the DOPO-g-PDA@SiO2 particles are replaced with an equal mass of aluminum phosphite, while the rest of the preparation steps are the same as in Example 1.

[0038] Comparative Example 2 The difference from Example 1 is that the DOPO-g-PDA@SiO2 particles are replaced with an equal mass of DOPO, while the rest of the preparation steps are the same as in Example 1.

[0039] Comparative Example 3 The difference from Example 1 is that the DOPO-g-PDA@SiO2 particles are replaced with PDA@SiO2 particles of equal mass, while the rest of the preparation steps are the same as in Example 1.

[0040] Comparative Example 4 The difference from Example 1 is that the DOPO-g-PDA@SiO2 particles were replaced with an equal mass of DOPO-g-SiO2 particles (DOPO was directly grafted onto the surface of nano-SiO2, without a PDA layer). The preparation method of DOPO-g-SiO2 was as follows: the PDA coating step was omitted, and the activated nano-SiO2 was directly reacted with the DOPO derivative under the same conditions. The remaining preparation steps were the same as in Example 1.

[0041] The polyamide resin composites prepared in Examples 1-6 and Comparative Examples 1-4 were tested for tensile strength, comparative tracking index, flame retardancy rating and thermal aging performance. The results are shown in Tables 1 and 2.

[0042] Tensile strength was tested according to the relevant methods of GB / T 1040.1-2018; notched impact strength was tested according to the relevant methods of GB / T 1843-2008, with test temperatures of room temperature (23℃) and low temperature (-40℃); heat distortion temperature was tested according to the relevant methods of GB / T 1634.1-2019, with a test load of 1.82 MPa; melt flow rate (MFR) was tested according to the relevant methods of GB / T 3682.1-2018, with test conditions of 320℃ × 2.16 kg; molding shrinkage was tested according to the relevant methods of ISO 294-4:2018, with shrinkage measured parallel to the melt flow direction (MD) and perpendicular to the melt flow direction (TD); dielectric strength was tested according to the relevant methods of GB / T 1408.1-2016; comparative tracking index (CTI) was tested according to the relevant methods of GB / T 4207-2022; flame retardancy rating was tested according to GB / T The insulation resistance adopts the relevant methods of GB / T 31838.2-2019; the dry heat aging performance adopts GB / T 7141-2008, the dry heat aging condition is 150℃×1000h, and the retention rate (%) = (performance value after dry heat aging / performance value before dry heat aging)×100%; the damp heat aging performance refers to the relevant methods of GB / T 2423.3-2016, using 85%RH×85℃×1000h as accelerated aging conditions, and the retention rate (%) = (performance value after damp heat aging / performance value before damp heat aging)×100%.

[0043] Table 1 Performance test results of Examples 1-6

[0044] Table 2 Performance test data for Comparative Examples 1-4

[0045] As can be seen from Examples 1-3, when the amount of polyamide resin (PA10T / 66) increases from 55 parts to 58 parts and then to 60 parts, the overall performance of the composite material is comprehensively improved.

[0046] A comparison of Examples 1, 4, and 5 shows that when the amount of DOPO-g-PDA@SiO2 particles decreased from 2.0 parts to 1.5 parts, tensile strength, notched impact strength, heat distortion temperature, dielectric strength, tensile retention rate after dry heat aging, CTI retention rate after dry heat aging, tensile retention rate after damp heat aging, and insulation resistance after damp heat aging all showed a decreasing trend, but the UL94 after aging remained V-0. When the amount of aluminum phosphite increased from 2.5 parts to 3.0 parts, tensile strength, notched impact strength, heat distortion temperature, dielectric strength, tensile retention rate after dry heat aging, tensile retention rate after damp heat aging, and insulation resistance after damp heat aging all showed an increasing trend, with a CTI retention rate of 94% after dry heat aging, and the UL94 after aging remained V-0.

[0047] As can be seen from the comparison between Example 6 and Examples 1 and 2, when the mass ratio of DOPO derivative to PDA@SiO2 in the preparation process of DOPO-g-PDA@SiO2 is reduced from 2:1 to 1.5:1, the grafting density decreases and the overall performance decreases slightly.

[0048] A comparison of Examples 1-6 with Comparative Examples 1-4 shows that simply replacing DOPO-g-PDA@SiO2 particles with unmodified DOPO, simply replacing DOPO-g-PDA@SiO2 particles with PDA@SiO2 particles, simply replacing DOPO-g-PDA@SiO2 particles with DOPO-g-SiO2 particles, or simply completely eliminating DOPO-g-PDA@SiO2 particles, cannot simultaneously achieve the comprehensive level of this invention in terms of flame retardancy rating, comparative tracking index, and long-term thermal aging stability.

[0049] The above results demonstrate and describe the basic principles and main features of this application, as well as its advantages.

[0050] Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the equivalents of the appended claims.

Claims

1. A preparation process for a polyamide resin composite material, characterized in that, Includes the following steps: S1. Dissolve DOPO and GPTMS in anhydrous toluene at a mass ratio of (1.2~1.8):1, with the mass ratio of anhydrous toluene to DOPO being (5~10):

1. Add 1%~5% of triethylamine by mass of DOPO and reflux under nitrogen protection. After the reaction is complete, distill under reduced pressure to obtain the DOPO derivative. Disperse PDA@SiO2 particles in anhydrous toluene solvent, with the mass ratio of anhydrous toluene to PDA@SiO2 particles being (10~20):

1. Add the DOPO derivative and 0.5%~2% of triethylamine by mass of the DOPO derivative, with the mass ratio of the DOPO derivative to PDA@SiO2 particles being (1~3):

1. React under nitrogen protection. After the reaction is complete, centrifuge, wash, and dry to finally obtain DOPO-g-PDA@SiO2 particles. S2. By weight, 55-60 parts of polyamide resin, 11-15 parts of flame retardant system, 3-4 parts of maleic anhydride grafted polyolefin elastomer, and 2-4 parts of functional additives are mixed at 800-1200 rpm for 3-5 minutes to obtain a mixture; the mixture is then extruded with 18-21 parts of flat glass fiber using a twin-screw extruder to obtain the polyamide resin composite material. The flame retardant system includes a flame retardant and a flame retardant synergist. The flame retardant is 8-10 parts of aluminum diethylphosphite, and the flame retardant synergist is 2-3 parts of aluminum phosphite and 1-2 parts of DOPO-g-PDA@SiO2 particles.

2. The preparation process of a polyamide resin composite material according to claim 1, characterized in that: The polyamide resin is one or two of polyamide 9T, polyamide 10T, polyamide 12T, and polyamide 10T / 66 copolymer.

3. The preparation process of a polyamide resin composite material according to claim 2, characterized in that: The polyamide resin is a polyamide 10T / 66 copolymer, and the mass ratio of polyamide 10T to polyamide 66 is (13~17):(3~7).

4. The preparation process of a polyamide resin composite material according to claim 1, characterized in that: The functional additives include 0.5-1 parts antioxidant, 0.2-0.5 parts lubricant, 0.3-0.5 parts acid absorber, 0.5-1 parts colorant, 0.2-0.5 parts nucleating agent, and 0.3-0.5 parts chain extender.

5. The preparation process of a polyamide resin composite material according to claim 4, characterized in that: The antioxidants include hindered phenolic antioxidants, phosphite antioxidants, and copper salt heat stabilizers; the hindered phenolic antioxidants are selected from one or more of antioxidant 1098, antioxidant 1076, and antioxidant 1010; the phosphite antioxidants are selected from one or more of antioxidant 168 and antioxidant 626; and the copper salt heat stabilizers include a combination of cuprous iodide and potassium iodide.

6. The preparation process of a polyamide resin composite material according to claim 5, characterized in that: The antioxidant comprises antioxidant 1098, antioxidant 168, and copper salt heat stabilizer; wherein antioxidant 1098 is 0.2 to 0.4 parts, antioxidant 168 is 0.2 to 0.4 parts, and copper salt heat stabilizer is 0.1 to 0.2 parts.

7. The preparation process of a polyamide resin composite material according to claim 4, characterized in that: The lubricant is one or more of pentaerythritol stearate and silicone masterbatch.

8. The preparation process of a polyamide resin composite material according to claim 4, characterized in that: The acid absorber is zinc oxide; the colorant is black masterbatch; the nucleating agent is talc; and the chain extender is ADR-4468.

9. The preparation process of a polyamide resin composite material according to claim 1, characterized in that: The PDA@SiO2 particles were prepared by the following method: nano-SiO2 was dispersed in 0.01 mol / L tris(hydroxymethyl)aminomethane buffer solution at pH 8-9, with a mass ratio of nano-SiO2 to tris(hydroxymethyl)aminomethane buffer solution of 1:(50-100). After ultrasonic dispersion, dopamine hydrochloride was added, with a mass ratio of dopamine hydrochloride to nano-SiO2 of (1-2):

1. After stirring and reaction, the particles were centrifuged, washed, and dried to obtain PDA@SiO2 particles.

10. The preparation process of a polyamide resin composite material according to claim 1, characterized in that: The temperatures of the twin-screw extruder in zones one through six are as follows: 275~285℃, 280~290℃, 280~290℃, 275~285℃, 265~275℃, 255~265℃; the screw speed is 280~320rpm.